2018
DOI: 10.1080/19390211.2018.1438553
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Garlic, Purple Onion, and White Onion on Key Enzymes Linked with Type 2 Diabetes and Hypertension

Abstract: Spices are used in soup preparation in many homes and serve as ingredients in the preparation of several traditional delicacies endowed with natural antioxidants such as polyphenols. The aim of this study is to evaluate the effect of aqueous extract of garlic, white onion, and purple onion on angiotensin-converting enzyme, α-amylase, and α-glucosidase activity in vitro and determine their antioxidant properties via various antioxidant assays such as OH, Fe chelation, and 2, 2'-azino-bis 3-ethylbenzothiazoline-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 31 publications
1
24
1
1
Order By: Relevance
“…ACE, another enzyme that have an important impact on metabolic syndrome, plays a pivotal role in the regulation of blood pressure (Villiger, Sala, Suter, & Butterweck, 2015). Several plants in Liliaceae family from Allium were found as a potential effective remedy of hypertension possibly due to the inhibitory effects on ACE (Oboh, Ademiluyi, Agunloye, Ademosun, & Ogunsakin, 2018). Plenty of synthetic drugs, such as captopril, that used in the treatment of hypertension were ACE inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACE, another enzyme that have an important impact on metabolic syndrome, plays a pivotal role in the regulation of blood pressure (Villiger, Sala, Suter, & Butterweck, 2015). Several plants in Liliaceae family from Allium were found as a potential effective remedy of hypertension possibly due to the inhibitory effects on ACE (Oboh, Ademiluyi, Agunloye, Ademosun, & Ogunsakin, 2018). Plenty of synthetic drugs, such as captopril, that used in the treatment of hypertension were ACE inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, searching for ACE-inhibitor from natural plants has been attacked much attention. Several plants in Liliaceae family from Allium were found as a potential effective remedy of hypertension possibly due to the inhibitory effects on ACE (Oboh, Ademiluyi, Agunloye, Ademosun, & Ogunsakin, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, phenolic acid improved NO bioavailability, increased catalase activity, and decreased glutathione level. Findings have demonstrated that hydroxyl and carboxyl groups, in phenolic acids, interact with Zn 2+ and the disulfide bridge residues at the active site of the ACE and prevents its activity (Oboh, Ademiluyi, Agunloye, Ademosun, & Ogunsakin, 2019).…”
Section: Phenolic Compounds In Berries and Their Antihypertensive Actmentioning
confidence: 99%
“…Similar results were reported by Zhang et al [232] in a study comparing white, yellow, and red onion, with the latter showing considerably higher total anthocyanin, flavonoid, and polyphenol content, which was also correlated to high antioxidant activity measured through DPPH, 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS• + ), and fluorescence recovery after photobleaching (FRAP) assays. Bulb extracts are potent bioactive natural matrices, and, according to the study of Oboh et al [233], extracts of purple onion were effective against angiotensin-converting enzyme, α-amylase, and α-glucosidase activity, showing significant antidiabetic and anti-hypertensive effects. Moreover, skins of pearl onion exhibited significant anti-inflammatory properties and inhibitory effects against radical-induced DNA scission [234].…”
Section: Onionmentioning
confidence: 99%